2020
DOI: 10.1016/j.jcmgh.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Hypergastrinemia Expands Gastric ECL Cells Through CCK2R+ Progenitor Cells via ERK Activation

Abstract: Background & Aims Enterochromaffin-like (ECL) cells in the stomach express gastrin/cholecystokinin 2 receptor CCK2R and are known to expand under hypergastrinemia, but whether this results from expansion of existing ECL cells or increased production from progenitors has not been clarified. Methods We used mice with green fluorescent protein fluorescent reporter expression in ECL cells (histidine decarboxylase [Hdc]-green fluorescent protein), as well as Cc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 59 publications
(74 reference statements)
0
37
0
Order By: Relevance
“…activation of the ERK pathway in progenitor cells. 100,101 Therefore, the tumor-promoting effects of gastrin in the proximal stomach probably occur via stimulation of CCK2R-expressing proliferating progenitors in the isthmus-neck region. Given that the serum gastrin level is usually elevated in patients with long-term proton pump inhibitor (PPI) use, increased gastric cancer risk in such patients might be affected by activation of the gastrin/CCK2R pathway.…”
Section: G a S Trinmentioning
confidence: 99%
“…activation of the ERK pathway in progenitor cells. 100,101 Therefore, the tumor-promoting effects of gastrin in the proximal stomach probably occur via stimulation of CCK2R-expressing proliferating progenitors in the isthmus-neck region. Given that the serum gastrin level is usually elevated in patients with long-term proton pump inhibitor (PPI) use, increased gastric cancer risk in such patients might be affected by activation of the gastrin/CCK2R pathway.…”
Section: G a S Trinmentioning
confidence: 99%
“…In the mouse corpus, Wnt5a-dependent noncanonical Wnt signaling appears to be involved in stem cell function [ 10 , 14 ]. While other pathways such as gastrin, acetylcholine, R-spondin, BMP signaling likely contribute to gastric stem cell niche [ 11 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ], accumulating evidence highlighted the importance of MAPK pathway in gut stem cells. For example, it has been reported that JNK is one of Wnt activators in the intestine and thus promotes epithelial proliferation and carcinogenesis [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parietal and chief cell loss is considered to alter the status of proliferation or differentiation in oxyntic glands, and lead to induce metaplastic changes [ 4 , 5 , 6 , 7 ]. Recent published papers have identified several stem cell markers in the stomach [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, it has been poorly understood how gastric stem/progenitor cells could differentiate to metaplasia or dysplasia during H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, since gastritis elevates gastrin, the normal upper level became too high [42]. Furthermore, there is no threshold for the tumorigenic effect of gastrin [51]. Both Helicobacter pylori infection and PPIs treatment alone or in combination may induce a degree of hypergastrinemia that in the long-term is sufficient to evoke gastric tumors based upon the gastrin values in patients with autoimmune gastritis and gastric NETs (carcinoids) [52].…”
Section: Gastric Cancermentioning
confidence: 99%